Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik CV Family Computer Menggunakan Metode WASPAS Dengan Pembobotan ROC - Sitepu, Riezky Dermawan Syam; Zebua, Taronisokhi (Jurnal Sains dan Teknologi Informasi, 2023)
The success and sustainability of a company greatly depend on the quality of its employees. However, in the competitive business world, selecting the best employees is not an easy task. To enhance efficiency and effectiveness in the employee selection process, many companies use a Decision Support System (DSS) as a tool. One of the methods used in the DSS is the Weighted Aggregated Sum Product Assessment (WASPAS) with the weighting method known as the Rank Order Centroid (ROC), due to the limitations and lack of precision in providing weighting values in the WASPAS method, the use of the ROC method is necessary in determining the weight values for criteria and subcriteria. Initially expressed as sentences, the criteria and subcriteria are transformed into numerical values based on the ROC calculation method. This article discusses the implementation of the DSS using the WASPAS method and ROC weighting in the selection of the best employees at CV Family Computer, a company in the information technology industry, this method combines weighting techniques with the ROC method and outlines the implementation steps in selecting the best employees at CV Family Computer. The results obtained after applying the ROC method are used to assign weights and determine the level of importance for each criterion. The WASPAS method is then applied to rank each alternative. Consequently, in this study of selecting the best employees, alternative A7, Danta Panjaitan, is identified with a value of 2.8857.